Do‐Not‐Resuscitate Orders in Older Adults During Hospitalization: A Propensity Score–Matched Analysis. Issue 5 (20th April 2018) - Patel, Karishma; Sinvani, Liron; Patel, Vidhi; Kozikowski, Andrzej; Smilios, Christopher; Akerman, Meredith; Kiszko, Kinga; Maiti, Sutapa; Hajizadeh, Negin; Wolf‐Klein, Gisele; Pekmezaris, Renee
Abstract : Objectives: To explore the effect of the presence and timing of a do‐not‐resuscitate (DNR) order on short‐term clinical outcomes, including mortality. Design: Retrospective cohort study with propensity score matching to enable direct comparison of DNR and no‐DNR groups. Setting: Large, academic tertiary‐care center. Participants: Hospitalized medical patients aged 65 and older. Measurements: Primary outcome was in‐hospital mortality. Secondary outcomes included discharge disposition, length of stay, 30‐day readmission, restraints, bladder catheters, and bedrest order. Results: Before propensity score matching, the DNR group (n=1, 347) was significantly older (85.8 vs 79.6, p<.001) and had more comorbidities (3.0 vs 2.5, p<.001) than the no‐DNR group (n=9, 182). After propensity score matching, the DNR group had significantly longer stays (9.7 vs 6.0 days, p<.001), were more likely to be discharged to hospice (6.5% vs 0.7%, p<.001), and to die (12.2% vs 0.8%, p<.001). There was a significant difference in length of stay between those who had a DNR order written within 24 hours of admission (early DNR) and those who had a DNR order written more than 24 hours after admission (late DNR) (median 6 vs 10 days, p<.001). Individuals with early DNR were less likely to spend time in intensive care (10.6% vs 17.3%, p=.004), receive a palliative care consultation (8.2% vs 12.0%, p=.02), be restrained (5.8% vs 11.6%, p<.001), have an order for nothing by mouth (50.1% vs 56.0%, p=.03), have a bladder catheter (31.7% vs 40.9%, p<.001), or die in the hospital (10.2% vs 15.47%, p=.004) and more likely to be discharged home (65.5% vs 58.2%, p=.01). Conclusion: Our study underscores the strong association between presence of a DNR order and mortality. Further studies are necessary to better understand the presence and timing of DNR orders in hospitalized older adults.